Improving Technology and Production Management in the Palm Sugar Craftsman Group in Rambah Tengah Hulu Village, Rokan Hulu Regency: Peningkatan Teknologi dan Manajemen Produksi Kelompok Pengrajin Gula Aren di Kabupaten Rokan Hulu - Nurrahmawati , Nurrahmawati; Kurniawan, Hendry; Defidelwina, Defidelwina Defidelwina (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Palm trees are one of the potential commodities to be developed in Indonesia, one of which is in Rambah Tengah Hulu Village, Rambah District, Rokan Hulu Regency. Usually, craftsmen process palm water into molded palm sugar. The survey results show that 16 palm sugar craftsmen in Rambah Tengah Hulu Village have joined the palm sugar craftsmen group. It's just that this group has not been active for a long time. The main problems found among palm sugar craftsmen are that the production process of processing palm sap into palm sugar still uses very simple technology, the size of the product produced is not yet uniform, and palm sugar craftsmen have never received training or counseling regarding management, planning and recording business finances, so it is necessary Efforts are made so that groups of palm sugar craftsmen can maximize their business development. The aim of implementing this service is to provide solutions in improving technology and management of palm sugar business production. The method for implementing this service is that first the craftsmen are given counseling about the importance of forming a group in a business, then the craftsmen are given counseling about financial planning and recording. Craftsmen also make furnaces and tools for molding palm sugar and are given assistance in using and maintaining them. The result of this community service activity is that the average understanding of partners about the importance of group formation, planning and recording finances has reached 77.95%. Craftsmen understand the use of applied technology and craftsmen understand planning and recording business finances, as can be seen from the increased understanding of participants before and after carrying out activities. Craftsmen also have uniform printing equipment and modified furnaces.Technology; production management; Palm sugar